Research Progress on the Regulation of Meat Quality and Application of Fermentation Technology for Meat Products - Zhengyu LONG; Jinhao ZOU; Huaigu YANG; Guopu REN; Qingming CAO; Daobang TANG (Shipin gongye ke-ji, 2024)
Fermentation is an important processing technology in the modern food industry, which can be used to produce fermented meat products on a large scale. This paper explores the role of fermentation technology in regulating the quality of meat products, and summarizes the current research and application of fermentation agents and fermentation processes in meat processing from three aspects: Screening and construction of fermentation agents, inoculation strategies of fermentation agents, factors affecting fermentation, and process optimization. It also discusses the development trend of fermentation technology in the application of meat products industry in China. Overall, the application of new fermentation technology will break the limitations of the traditional meat industry. In the future, people can adjust the fermentation processes and strategies for the demand characteristics of different fermented meat product qualities to produce nutritious, delicious, safe, and diverse fermented meat products that meet the needs of modern people’s life.